Clinician survey of language sampling practices in Australia - Westerveld, M.; Claessen, Mary (Informa Healthcare, 2014)
A national online survey was used to investigate spontaneous language sampling and analysis practices by speech-language pathologists working with children and adolescents. A total of 257 responses were received from clinicians around Australia. Results indicated that spontaneous language samples are collected on a routine basis in elicitation contexts deemed appropriate to the clients’ age or developmental stage. However, language samples were generally short, often not recorded, and analysed informally. Consistent with previous research into language sampling practices, the main barrier to more detailed language sample analysis appears to be the time needed for transcription. Despite rapid technological advances in the last two decades, only 12.5% of the respondents reported using computer-assisted transcription and analysis procedures. Suggestions are made on how to promote change in clinical practice to ensure spontaneous language samples are transcribed and analysed in more detail. By transcribing the samples, detailed analysis of children’s language performance can be undertaken, allowing for effective goal-setting and assisting in objective progress measuring during and following intervention.